CBPR Implementation Framework for Community‐Academic Partnerships. Issue 3 (6th April 2021) - Sánchez, Victoria; Sanchez‐Youngman, Shannon; Dickson, Elizabeth; Burgess, Ellen; Haozous, Emily; Trickett, Edison; Baker, Elizabeth; Wallerstein, Nina
Abstract: The Engage for Equity (E2) study is an intervention trial for community–academic research partnerships that seeks to improve partnering practices and health equity outcomes by providing community and academic partners with tools to enhance and advance power sharing and health equity. Twenty‐five community/academic research teams completed a two‐day training intervention where they were introduced to the CBPR Conceptual Model and corresponding applied tools to their partnerships. We report on team interviews conducted immediately after the training, where teams discussed opportunities and challenges using the CBPR Model as an implementation framework as they considered their own contexts, their partnering processes/practices, actions, and their desired outcomes. We applied Diffusion of Innovation theory to guide data collection and analysis; augmented by intent to use and collective reflection. Results pointed to the flexibility of the CBPR model, concrete use of tools (e.g., planning/evaluation), and broader use in inspiring collective reflection to improve partnering practices and inform equity values. As an implementation framework, the CBPR model incorporates collaborative processes and strategies to mitigate power differentials into key phases of implementation studies, adding factors central to health equity work, not existing in previous implementation frameworks. Highlights: Community‐based participatory research can enhance implementation science. The CBPR framework facilitates collective empowerment in community/academic partnerships. Participants noted how the CBPR model and flexibility of tools can improve partnering practices.